Immunogenicity of 13-valent pneumococcal conjugate vaccine among children with underlying medical conditions. Issue 34 (3rd August 2017) - Jallow, Sabelle; Madhi, Shabir A.; Madimabe, Richard; Sipambo, Nosisa; Violari, Avy; Kala, Udai; Petersen, Karen; Naidoo, Sanushka; Verwey, Charl; Moore, David P.; Nunes, Marta C.
Highlights: Children with chronic disease are at risk of pneumococcal disease. PCV13 immunogenicity data for children with chronic disease is scarce. One PCV13 dose elicited immunogenic responses in the at-risk children. In children with kidney or lung disease no improved immune response post-second dose. In HIV-infected children a second PCV13 dose elicited higher GMCs but no increase in percentage of responders. Abstract: Background: Streptococcus pneumoniae is a leading cause of vaccine-preventable disease in children under 5 years. Immunocompromised children and those with underlying diseases are at increased risk of severe complications from vaccine-preventable infections. We studied the humoral immune response to the 13-valent pneumococcal conjugate vaccine (PCV13) in children with HIV-infection, kidney or lung disease and compared this to the response in healthy control children. Methods: Children aged 12–71 months with underlying conditions including HIV-infection and those with kidney and lung diseases (at-risk children), and a healthy control group were vaccinated with PCV13. The at-risk children received two doses of PCV13 and the controls received one dose. Serotype-specific antibodies for all PCV13 serotypes were measured by a luminex-based enzyme immunoassay at baseline and post-vaccination. Results: After the first PCV13 dose, the fold-increase in serotype-specific antibody geometric mean concentrations (GMCs) from baseline and the percentage of participants with ≥4-fold-increase in antibody concentrations was similar between the control and at-risk children. GMCs were, however, lower for three of the 13 serotypes in HIV-infected children, higher for serotype 6B in children with kidney disease and higher for serotypes 6B and 14 in children with lung disease. After second vaccine dose HIV-infected children had an increase in GMCs from post-first dose for nine serotypes but the percentage of participants with ≥4-fold-increase from baseline was similar post-second dose compared to post-first dose except for serotypes 6A and 19F. In children with kidney or lung diseases the immune responses after second vaccine dose were similar to post-first dose. Attenuated responses were observed for serotypes 3 and 19A in all study-groups, which was especially pronounced in the at-risk groups. Conclusion: All study-groups mounted an immune response to PCV13, with the at-risk groups having responses that were mostly similar to the control children.